Female Infertility: A Study of Risk Factors. - Abdul-Kader, Rasha A.; Ajeel, Narjis A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Infertility is a relatively common condition. It can be attributed to factors in a female partner, a male partner, or in both partners. However, certain socio-demographic and life style factors have been linked to female infertility. Objective: To determine the association between female infertility and selected risk factors. J Fac Med Baghdad 2014; Vol.56, No. 2 Received June.2013 Accepted Oct.2013 Patients and Methods: This is a case – control study carried out in Basrah Governorate over a period of ten months, from 1st of January to 31st of October, 2006. Cases were married women who had no pregnancy for at least one year (infertile women), a total of 212 cases were included. The controls were married women who had babies aged less than one year (fertile women); the total number of controls was 213. Results: the study found that the risk of infertility increases steadily with the increase in age. The risk of female infertility also increased in women with menstrual cycle disturbances (like irregular menstrual cycle length and scanty or heavy menstrual blood loss), women with previous history of abortion, women with previous caesarean section, and in women with previous history of ectopic pregnancy. Infertility was also found to be associated with obesity and with daily caffeine consumption. Conclusion: the independent risk factors for female infertility were history of previous CS, menstrual cycle disturbance, regular daily caffeine intake and obesity.